Association Between Walking Pace and Stroke Incidence: Findings From the UK Biobank Prospective Cohort Study. Issue 5 (May 2020) - Hayes, Sara; Forbes, John F.; Celis-Morales, Carlos; Anderson, Jana; Ferguson, Lyn; Gill, Jason M.R.; Gray, Stuart; Hastie, Claire; Iliodromoti, Stamatina; Lyall, Donald; Pellicori, Pierpaolo; Sattar, Naveed; et al.
Abstract : Background and Purpose—: Stroke incidence in younger and middle-aged people is growing. Despite this, its associations in this subset of the stroke population are unknown, and prevention strategies are not tailored to meet their needs. This study examined the association between self-reported walking pace and incident stroke. Methods—: Data from the UK Biobank were used in a prospective population-based study. Three hundred and sixty-three thousand, one hundred and thirty-seven participants aged 37 to 73 years (52% women) were recruited. The associations of self-reported walking pace with stroke incidence over follow-up were investigated using Cox proportional-hazard models. Results—: Among 363, 137 participants, 2705 (0.7%) participants developed a fatal or nonfatal stroke event over the mean follow-up period of 6.1 years (interquartile range, 5.4–6.7). Slow walking pace was associated with a higher hazard for stroke incidence (hazard ratio [HR], 1.45 [95% CI, 1.26–1.66]; P <0.0001). Stroke incidence was not associated with walking pace among people <65 years of age. However, slow walking pace was associated with a higher risk of stroke among participants aged ≥65 years (HR, 1.42 [95% CI, 1.17–1.72]; P <0.0001). A higher risk for stroke was observed on those with middle (HR, 1.28 [95% CI, 1.01–1.63]; P =0.039) and higher (HR, 1.29 [95% CI, 1.05–1.69]; P =0.012) deprivation levels but not in the least deprived individuals. Similarly, overweight (HR, 1.30 [95% CI, 1.04–1.63]; P =0.019) and obese (HR, 1.33 [95% CI, 1.09–1.63]; P =0.004) but not normal-weight individuals had a higher risk of stroke incidence. Conclusions—: Slow walking pace was associated with a higher risk of stroke among participants over 64 years of age in this population-based cohort study. The addition of the measurement of self-reported walking pace to primary care or public health clinical consultations may be a useful screening tool for stroke risk.